2018
DOI: 10.1002/hpm.2689
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting job satisfaction among medical laboratory technologists in University Hospital, Oman: An exploratory study

Abstract: SummaryBackgroundThe worldwide shortage of health care professionals has prompted Oman to recruit such professionals from other countries. Among such professionals, medical laboratory technologists are key in effective health care delivery, and it is therefore important to discover what influences the job satisfaction enjoyed by them. However, little research has been undertaken in this area; consequently, this study explores the factors that impact upon job satisfaction among medical laboratory technologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The findings regarding the participants' feelings are consistent with those reported in a previous study performed at the University Hospital in Oman (Alrawahi et al, 2018). As noted by Kosteas (2010), promotions are the main mechanism for achieving worker retention and satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…The findings regarding the participants' feelings are consistent with those reported in a previous study performed at the University Hospital in Oman (Alrawahi et al, 2018). As noted by Kosteas (2010), promotions are the main mechanism for achieving worker retention and satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Because of the high importance of job satisfaction, numerous job‐satisfaction studies have been conducted in healthcare in many countries for physicians and nurses . There have been also some studies for pharmacists and a few for technologists . From these studies, we know that healthcare employee satisfaction is not only affected by national culture and other nation‐dependent factors, such as laws, regulations, and healthcare systems, but also by work‐related factors (eg, work demands, autonomy, and role ambiguity), organisational factors (eg, management rules, styles, and environment), and staff individual factors (eg, profession, age, and job experience).…”
Section: Introductionmentioning
confidence: 99%
“…Employees who are from dominant groups in the organization tend to be more satisfied with their jobs because their managers and coworkers tend to provide them with more feedback and support [35]. Scholars have also revealed that employees at the establishment career stage are more likely to expect to become accepted as equal and regular members of the organization by building an effective relationship with coworkers and supervisors, thus learning organizational norms and values better [36]. Although research on social decision making has already shown that trust on a third party affects the individual's cooperative behavior [37], studies have suggested that employees' perception of both co-workers and supervisory support may bring different outcomes, which means that employees' trust towards their co-workers and supervisors varies in general working place [38].…”
Section: Interpersonal Relationshipmentioning
confidence: 99%